1986
DOI: 10.1021/jf00068a053
|View full text |Cite
|
Sign up to set email alerts
|

Legumes and a cereal with high methionine/cysteine contents

Abstract: The amino acid and chemical composition of seeds from three lesser known legume species and an African cereal with high Met + Cys contents is presented. Mesquite (Prosopis spp.): 41% protein, 2.5% Met + Cys. Djenkol bean (Pithecellobium lobatum): immature seeds, 32% protein, 2.8% Met + Cys; mature seeds, 16% protein, 3.9% Met + Cys. Tamarind seeds (Tamarindus indica): 18% protein, 3.5% Met + Cys. Acha (Digitaria exilis): 8% protein, 7.3% Met + Cys. Threonine is the first limiting amino acid for mesquite and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 3 publications
3
18
0
1
Order By: Relevance
“…Vijayakumari et al(1997) reported that 513 mg of phytic acid is present in 100 g of P. chilensis. P. chilensis is a legume that is very rich in methionine and cystine (de Lumen et al, 1986). Enujiugha and Ayodele-Oni (2003) reported that tannin was not detected in C. forda.…”
Section: Resultsmentioning
confidence: 99%
“…Vijayakumari et al(1997) reported that 513 mg of phytic acid is present in 100 g of P. chilensis. P. chilensis is a legume that is very rich in methionine and cystine (de Lumen et al, 1986). Enujiugha and Ayodele-Oni (2003) reported that tannin was not detected in C. forda.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, this tribal pulse deserves further study, since it can be used as a genetic resource to improve the protein quality of other plant foods through molecular biology techniques, as it is expected that the high methionine cystine content might be due to sulphur amino acid-rich protein. 56 In general, a characteristic amino acid pro®le of high glutamic and aspartic acid content in the Gila bean seed kernel is common in both albumin and globulin fractions as discussed above. However, each of the fractions is distinct with respect to its amino acid composition.…”
Section: Amino Acid Profiles and Starch Fractionsmentioning
confidence: 99%
“…The seeds of Pithecellobium species are traditionally used worldwide as both a food and a feedstuff (Candlish et al 1987;Misra and Nigam 1978;De Lumen et al 1986;Rackis et al 1986;Sotelo et al 1990;Toure et al 1998 . 13) (Ma et al 2008).…”
Section: In the Genus Pithecellobiummentioning
confidence: 99%